Customer Satisfaction Mediation: Brand Image and Perceived Value on Behavioral Intention - Muhammad Irfan Nasution; Elsa Laura Rizky Barona; Salsabila Azzahra; Nurul Aulia (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
This study aims to determine the impact of the variable Brand Image and Perceived Value against Behavioral Intention with Customers Satisfaction as an intervening variable in the MS Glow beauty clinic in Medan. The descriptive and verificative method is used in this study research. The object of this research is the citizen that lived at Bumi Asri who use MS Glow products the total is unknown and it can be almost 100 samples. Data were collected in this research with a questionnaire to all respondents using the accidental sampling technique. Data processing using the SEM approach PLS basis with SmartPLS 3.0. device. The data result analysis indicates that Brand Image had positive points and is significant against Behavioral Intention. Brand Image also had positive points and significance against Customers Satisfaction, and Customer satisfaction has positive point and significance against Behavioral Intention. Perceived Value takes a positive point effect but is not significant against Behavioral Intention. Perceived Value takes a positive point effect and is significant against Customers Satisfaction.